Lithium ion battery negative electrode material and preparation method and application thereof

By coating the outer layer of nano-silicon with graphene and blending it with graphite, the structural damage caused by volume changes and overgrowth of SEI films is solved, and high specific capacity, high first-time Coulomb efficiency and cyclic stability are achieved. Lithium ion battery negative electrode material.

CN119447208APending Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310974623.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode material silicon has caused structural damage due to volume changes and overgrowth of SEI films, which limits its application in lithium-ion batteries.

Method used

Modified nanosilicon, whose core is nanosilicon, and the outer layer is coated with graphene, which is blended with graphite to improve electrochemical stability and specific capacity.

Benefits of technology

The first Coulomb efficiency and cycle stability of lithium-ion battery negative electrode materials are improved, the cost is reduced, and the performance of graphite negative electrode materials is matched.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447208A_ABST
    Figure CN119447208A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery negative electrode material which is formed by blending graphite and modified nano silicon, and the outermost layer of the modified nano silicon is coated with graphene, so that the specific capacity and the first coulombic efficiency are high, and the blending performance of the nano silicon and the graphite negative electrode material is improved; the specific capacity of the blended negative electrode material can be conveniently adjusted according to needs, the first coulombic efficiency is high when the blended negative electrode material is used as a lithium ion battery negative electrode material, the cycling stability is good, and the performance adjustment is convenient and easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries and discloses a lithium ion battery negative electrode material and a preparation method and application thereof. Background Art

[0002] The growing lithium-ion battery market has continuously put forward higher requirements for battery performance, especially battery energy density. As the carrier of battery performance, the specific capacity of electrode materials is crucial to battery energy density. However, as the current commercial negative electrode material, graphite has a theoretical specific capacity of only 372mAh·g -1 , which can no longer meet the urgent market demand for high energy density. The theoretical specific capacity of silicon is much higher than that of graphite, but the huge volume change during charging and discharging can easily lead to silicon fragmentation and pulverization. On the one hand, it can destroy the electrode material structure and make silicon lose electrical contact; on the other hand, it can cause excessive growth of SEI film and consume a large amount of electrolyte. This leads to problems such as low initial coulombic efficiency and poor cycle stability when silicon is used as a negative electrode material for lithium-ion batteries, which greatly limits the application of silicon in lithium-ion batteries.

[0003] Nanosilicon prepared after silicon nano-sizing can significantly inhibit the adverse effects of silicon volume change and improve the cyclic stability of silicon. However, nanosilicon has a large specific surface area and is easy to agglomerate. At the same time, nanosilicon particles are easily oxidized to form silicon dioxide, which reduces the silicon specific capacity and the first coulombic efficiency. Therefore, it is necessary to coat and modify nanosilicon. On the one hand, it can improve the stability of nanosilicon in the air. On the other hand, it can improve the organic bonding of nanosilicon with materials such as binders, conductive agents and graphite during use, such as in the pulping process, to improve the electrochemical stability of nanosilicon as a negative electrode material for lithium-ion batteries.

[0004] Blending refers to the physical mixing of multiple materials. Blending has the advantages of simple operation and convenient performance regulation. However, high-capacity materials usually have a large volume change during charging and discharging, and it is difficult to produce ideal negative electrode materials by direct blending. In addition, the performance of positive and negative electrode materials needs to be reasonably matched. This field hopes to fully utilize the advantages of existing graphite negative electrode materials, such as stable structure, small volume change, and good conductivity, and meet the current market demand at a lower cost. Summary of the invention

[0005] The purpose of the present invention is to provide a negative electrode material for a lithium ion battery, which is a mixture of graphite and modified nano-silicon, has the characteristics of high initial coulombic efficiency and good cycle stability, and the specific capacity can be adjusted and matched with the graphite negative electrode material as needed, and the cost can also be lower.

[0006] Nano-sizing alone cannot completely solve the problem of silicon expansion, and the increase in specific surface area brings about the problem of reduced initial coulombic efficiency. The commercialization of silicon negative electrodes must further solve these technical problems. Silicon and graphite have different structural properties. The direct blending of the two is intrinsically difficult to be uniform, which increases the volatility of material properties. The same is true for amorphous carbon-coated nano-silicon. To achieve the purpose of the present invention, the present invention first provides a modified nano-silicon with a very high specific capacity, wherein the core is nano-silicon and the outermost layer is graphene, which can more effectively inhibit silicon expansion and ensure good lithium ion transmission performance, and the outermost layer of graphene is closer to the structural properties of graphite, so that the modified nano-silicon and graphite are blended more uniformly and have good electrical contact. The aforementioned modified nano-silicon has excellent performance and better compatibility with graphite negative electrode materials, thereby completing the present invention.

[0007] The main contents of the present invention are as follows.

[0008] 1. A negative electrode material for a lithium-ion battery, comprising modified nano-silicon and graphite, wherein the modified nano-silicon is nano-silicon with a heterogeneous carbon layer coated on the outer surface, the inner layer of the heterogeneous carbon layer is amorphous carbon, and the outer layer is graphene.

[0009] 2. According to the aforementioned negative electrode material, wherein, based on the negative electrode material, the mass fraction of the modified nano-silicon is 1% to 25%, and the mass fraction of the graphite is 75% to 99%; preferably, the mass fraction of the nano-silicon is 1% to 20%, and the mass fraction of the graphite is 80% to 99%; preferably, the mass fraction of the modified nano-silicon is 1% to 8%, and the mass fraction of the graphite is 92% to 99%.

[0010] 3. According to any of the aforementioned negative electrode materials, wherein the mass fraction of silicon in the modified nano-silicon is 60% to 80%, and the mass fraction of carbon is 10% to 30%.

[0011] 4. According to any of the above-mentioned negative electrode materials, wherein the heterogeneous carbon layer contains nitrogen, and in the XPSN1s analysis of the modified nano-silicon, the molar fraction of pyrrolic nitrogen is 70% to 90% based on the total molar amount of nitrogen species.

[0012] 5. According to any of the aforementioned negative electrode materials, wherein the mass fraction of nitrogen in the modified nano-silicon is 0.5% to 5%, and the mass fraction of oxygen is 1% to 10%; preferably, the mass fraction of nitrogen is 0.2% to 1%, and the mass fraction of oxygen is 1% to 5%.

[0013] 6. According to any of the aforementioned negative electrode materials, the median particle size of the modified nano-silicon is 5nm to 150nm.

[0014] 7. According to any of the aforementioned negative electrode materials, the thickness of the heterogeneous carbon layer is 3nm to 8nm.

[0015] 8. According to any of the aforementioned negative electrode materials, the thickness of the graphene is 1 nm to 6 nm.

[0016] 9. A method for preparing a negative electrode material for a lithium ion battery, comprising:

[0017] S1: dispersing elemental silicon in a solution containing a first carbon source, and obtaining nano-silicon slurry by mechanical crushing; the first carbon source is an organic carboxylic acid or carboxylic acid ester containing a hydroxyl group;

[0018] S2: adding dopamine or its ammonium salt to the nano-silicon slurry obtained in S1 to react and obtain a nano-silicon precursor;

[0019] S3 calcines the nano-silicon precursor in S2 at a high temperature under an inert gas to obtain modified nano-silicon;

[0020] S4 mixes the modified nano silicon prepared in S3 with graphite to obtain the negative electrode material for the lithium ion battery.

[0021] 10. According to the aforementioned preparation method, wherein the elemental silicon is single crystal silicon or polycrystalline silicon.

[0022] 11. According to any of the above-mentioned preparation methods, wherein, in S1, the first carbon source is selected from one or more of tartaric acid, citric acid, lactobionic acid, malic acid and ascorbic acid; and the mass ratio of the first carbon source to silicon is 1:0.2 to 1:5.

[0023] 12. A preparation method according to any of the above, wherein the mechanized crushing method is sand grinding, and the particle size of the silicon after sand grinding is 5nm to 150nm.

[0024] 13. A preparation method according to any of the above, wherein, in S1, the solvent is ethanol, isopropanol, n-butanol, hexane or cyclohexane.

[0025] 14. A preparation method according to any of the above, characterized in that the mass ratio of dopamine or its ammonium salt to the first carbon source is 0.3:1 to 1.2:1.

[0026] 15. According to any of the above-mentioned preparation methods, wherein, in S2, the solvent is removed after the reaction to obtain the nano-silicon precursor, and the solvent is removed by spray drying.

[0027] 16. According to any of the above-mentioned preparation methods, wherein, in S3, the temperature of the high-temperature calcination is 800°C to 1000°C.

[0028] 17. According to any of the aforementioned preparation methods, wherein, in S4, the graphite is natural graphite or artificial graphite.

[0029] 18. According to any of the above preparation methods, wherein, in S4, the mass ratio of modified nano-silicon to graphite is 1:3 to 1:99, preferably 1:4 to 1:99, and more preferably 1:11.5 to 1:99.

[0030] 19. A negative electrode material for a lithium-ion battery, prepared by any of the above methods.

[0031] 20. A negative electrode for a lithium ion battery, comprising any one of the negative electrode materials described above.

[0032] 21. A lithium ion battery comprising any one of the above-mentioned negative electrode materials.

[0033] Compared with the prior art, the present invention firstly manufactures a modified nano-silicon with a novel structure, wherein the core is nano-silicon and the outermost layer is coated with graphene. The graphene coating layer provides both sufficient strength and good conductivity, and can avoid direct contact between nano-silicon and electrolyte, and effectively reduce the electrolyte consumption caused by the breakage and generation of SEI film caused by the continuous expansion and contraction of silicon during the charging and discharging process. At the same time, since the outermost layer of graphene is more similar to the structural properties of graphite, the modified nano-silicon and the graphite negative electrode material are more uniformly blended and have good electrical contact. When it is used as a high-capacity component in the negative electrode material of a lithium-ion battery and is blended with graphite, a lithium-ion battery negative electrode material with appropriate specific capacity, high initial coulomb efficiency and stable cycle performance can be obtained.

[0034] Other features and advantages of the present invention will be described in detail in the detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a TEM image of the modified nano-silicon in the present invention.

[0036] Figure 2 This is the XPS N1s spectrum of the modified nano-silicon in the present invention.

[0037] Figure 3 This is the first charge and discharge curve of the negative electrode material prepared according to the method of Preparation Example 1.

[0038] Figure 4 TEM image of modified nano-silicon obtained without using dopamine compared with the present invention.

[0039] Figure 5 TEM image of modified nano-silicon obtained when the first carbon source is not used compared with the present invention.

[0040] Figure 6 This is the XRD pattern of the negative electrode material prepared according to the method of Preparation Example 1.

[0041] Figure 7This is the charge and discharge cycle curve of the negative electrode material prepared according to the method of Preparation Example 1. DETAILED DESCRIPTION

[0042] The present invention is described in detail below in conjunction with specific implementations, but it should be noted that the protection scope of the present invention is not limited by these specific implementations and principle explanations, but is determined by the claims.

[0043] Any embodiment described in this article may be freely combined with one or more other embodiments described in this article, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this article, unless a person skilled in the art considers it to be obviously unreasonable.

[0044] All features disclosed herein may be combined in any combination, and these combinations shall be deemed to be specifically disclosed and recorded by the present invention, unless considered by a person skilled in the art to be obviously unreasonable. The numerical points disclosed herein, unless otherwise specified, include not only the numerical points specifically disclosed in the embodiments, but also the endpoints of each numerical range in the specification, and the range of any combination of these numerical points shall be deemed to be the range disclosed or recorded by the present invention.

[0045] The technical and scientific terms used herein shall be based on their definitions if defined, and shall be understood according to the common meaning in the art if not defined.

[0046] The term "nanosilicon" is defined as silicon having a median particle size (D50) of 5 nm to 500 nm.

[0047] The term "graphene" refers to a layered carbon structure with a thickness of less than 10 nm, rather than an amorphous structure, which can be clearly observed under a high-resolution transmission electron microscope, and the interlayer spacing is approximately 0.33 nm to 0.34 nm.

[0048] The term "inert gas" is defined as a gas that has no appreciable effect on the electrochemical properties of a material.

[0049] The term "soluble" means soluble in the solvent in which it is used.

[0050] The present invention hereby introduces the contents of Chinese patent application CN 202310655946.0 in its entirety, and the modified nano-silicon in the present invention is the nano-silicon-carbon composite material in the Chinese application.

[0051] The first aspect of the present invention provides a negative electrode material for a lithium ion battery, comprising modified nano-silicon and graphite, wherein the modified nano-silicon is nano-silicon coated with a heterogeneous carbon layer on the outer surface, wherein the inner layer of the heterogeneous carbon layer is amorphous carbon and the outer layer is graphene.

[0052] According to the negative electrode material of the first aspect of the present invention, based on the negative electrode material, the mass fraction of the modified nano-silicon is 1% to 25%, and the mass fraction of the graphite is 75% to 99%; preferably, the mass fraction of the modified nano-silicon is 1% to 20%, and the mass fraction of the graphite is 80% to 99%; more preferably, the mass fraction of the modified nano-silicon is 1% to 8%, and the mass fraction of the graphite is 92% to 99%.

[0053] According to the negative electrode material of the first aspect of the present invention, there is no particular limitation on graphite, and any graphite that can be used commercially as a negative electrode material for lithium-ion batteries can be used. The graphite can be natural graphite or artificial graphite.

[0054] According to the modified nano-silicon in the first aspect of the present invention, the two-dimensional plane of the graphene is in a covering orientation relative to the surface of the modified nano-silicon.

[0055] According to the modified nano-silicon in the first aspect of the present invention, there is no limitation on the form of the nano-silicon, which may be nanoparticles, nanowires or nanosheets.

[0056] According to the modified nano-silicon in the first aspect of the present invention, the median particle size of the modified nano-silicon is 5 nm to 150 nm, preferably 30 nm to 100 nm.

[0057] According to the modified nano-silicon in the first aspect of the present invention, the mass fraction of silicon in the modified nano-silicon is 60% to 80%, and the mass fraction of carbon is 10% to 30%; preferably, the mass fraction of silicon is 70% to 80%, and the mass fraction of carbon is 10% to 20%.

[0058] According to the modified nano-silicon in the first aspect of the present invention, in some embodiments, the mass fraction of silicon in the modified nano-silicon is 60% to 80%, the mass fraction of carbon is 10% to 30%, the mass fraction of nitrogen is 0.5% to 5%, and the mass fraction of oxygen is 1% to 10%.

[0059] According to the modified nano-silicon in the first aspect of the present invention, in some embodiments, the mass fraction of silicon in the modified nano-silicon is 70% to 80%, the mass fraction of carbon is 10% to 20%, the mass fraction of nitrogen is 1% to 2%, and the mass fraction of oxygen is 4% to 9%.

[0060] According to the modified nano-silicon in the first aspect of the present invention, the heterogeneous carbon layer contains nitrogen.

[0061] According to the modified nano-silicon in the first aspect of the present invention, in some embodiments, in the XPS N1s analysis of the modified nano-silicon, the molar fraction of pyrrolic nitrogen is 70% to 90% based on the total molar amount of nitrogen species. It is believed that pyrrolic nitrogen is more conducive to lithium ion transmission and can further improve the conductivity of the carbon layer.

[0062] According to the modified nano-silicon in the first aspect of the present invention, the thickness of the heterogeneous carbon layer is 2nm to 10nm, preferably 3nm to 8nm.

[0063] According to the modified nano-silicon in the first aspect of the present invention, the thickness of the graphene is 1 nm to 6 nm, preferably 2 nm to 5 nm.

[0064] According to the modified nano silicon in the first aspect of the present invention, the secondary particle size of the modified nano silicon can be 1 μm to 5 μm. The secondary particle size is related to the drying form and operating conditions of the modified nano silicon. For example, by using different types of spray dryers and different operating conditions, products with different secondary particle sizes can be obtained. These are all existing knowledge in the field, and those skilled in the art can select appropriate equipment and operating conditions according to actual needs.

[0065] A second aspect of the present invention provides a method for preparing a negative electrode material for a lithium ion battery, comprising:

[0066] S1: dispersing elemental silicon in a solution containing a first carbon source, and obtaining nano-silicon slurry by mechanical crushing; the first carbon source is an organic carboxylic acid or carboxylic acid ester containing a hydroxyl group;

[0067] S2: adding dopamine or its ammonium salt to the nano-silicon slurry obtained in S1 to react and obtain a nano-silicon precursor;

[0068] S3, under an inert gas, calcining the nano-silicon precursor in S2 at a high temperature to obtain the modified nano-silicon;

[0069] S4 mixes the modified nano silicon prepared in S3 with graphite to obtain the negative electrode material for the lithium ion battery.

[0070] According to the preparation method provided in the second aspect of the present invention, there is no particular limitation on the form of elemental silicon, which may be single crystal silicon and / or polycrystalline silicon.

[0071] According to the preparation method provided by the second aspect of the present invention, the first carbon source is a hydroxyl-containing organic carboxylic acid or carboxylate. The present invention has found that adding a hydroxyl-containing organic carboxylic acid or carboxylate during the mechanical crushing process can inhibit the oxidation of silicon during the crushing process. It is believed that the hydroxyl-containing organic carboxylic acid or carboxylate reacts with the highly reactive silicon sites generated in situ during the crushing, uniformly covers the silicon surface, and reduces the reaction of silicon with alcohol solvents or trace oxygen in the environment. At the same time, the surface of mechanically crushed silicon is rough, and it is relatively flat after being treated with the first carbon source.

[0072] According to the preparation method provided by the second aspect of the present invention, in S1, the first carbon source can be selected from one or more of tartaric acid, citric acid, lactobionic acid, malic acid and ascorbic acid, preferably ascorbic acid. Preferably, the mass ratio of the first carbon source to silicon is 1:0.2 to 1:5, preferably 1:0.5 to 1:5.

[0073] According to the preparation method provided in the second aspect of the present invention, the mechanized crushing method is preferably sand milling. In some embodiments, the particle size of the silicon after sand milling can be 5nm to 150nm, generally 30nm to 100nm.

[0074] According to the preparation method provided in the second aspect of the present invention, in S1, the solvent is ethanol, isopropanol, n-butanol, hexane, cyclohexane or isooctane; preferably isopropanol or ethanol.

[0075] According to the preparation method provided in the second aspect of the present invention, in some embodiments, in S1, the solid content calculated as silicon is 2% to 20%, preferably 3% to 15%.

[0076] According to the preparation method provided by the second aspect of the present invention, the abundant alcoholic hydroxyl groups and carboxyl hydroxyl groups in the first carbon source have a strong binding force with the phenolic hydroxyl groups and amino groups in dopamine, so that dopamine is evenly distributed on the surface of the nano-silicon precursor.

[0077] According to the preparation method provided in the second aspect of the present invention, the mass ratio of dopamine or its ammonium salt to the first carbon source is 0.1:1 to 2:1, preferably 0.3:1 to 1.2:1, and more preferably 0.4:1 to 1:1.

[0078] According to the preparation method provided in the second aspect of the present invention, in S2, the reaction temperature is room temperature, such as 20°C to 40°C.

[0079] According to the preparation method provided by the second aspect of the present invention, in S2, the solvent is removed after the reaction to obtain the nano-silicon precursor. The present invention has no limitation on the method of removing the solvent, and spray drying is preferred.

[0080] According to the preparation method provided in the second aspect of the present invention, the temperature of the high-temperature calcination is 800°C to 1000°C.

[0081] The third aspect of the present invention provides a negative electrode material for a lithium ion battery prepared according to any of the aforementioned preparation methods.

[0082] A fourth aspect of the present invention provides a lithium ion battery negative electrode, which contains any of the aforementioned lithium ion battery negative electrode materials.

[0083] A fifth aspect of the present invention provides a lithium-ion battery, which contains any of the aforementioned lithium-ion battery negative electrode materials.

[0084] The present invention will be described in more detail below through examples.

[0085] The carbon layer structure on the surface of modified nano-silicon was characterized by transmission electron microscopy (TEM). The model of the TEM used was JEM-2100 (JEOL Ltd.), and the test conditions of the transmission electron microscopy were: the acceleration voltage was 200 kV.

[0086] Instruments and methods for elemental analysis: Carbon content was tested on a TA5000 thermal analyzer in an air atmosphere with a heating rate of 10°C / min over a temperature range from room temperature (25°C) to 1000°C. Nitrogen and oxygen content were tested on an ON5500 nitrogen and oxygen analyzer produced by Gangyan NAK Testing Technology Co., Ltd. with high-purity helium as the carrier gas.

[0087] Instrument and method for particle size test: The average particle size of nano silicon after sand grinding was measured by the British Mastersizer 3000 particle size analyzer, and the parameter setting was: the light shielding degree was 5.99%. The average particle size of the finished material was measured by the British Mastersizer 2000 particle size analyzer, and the parameter setting was: the light shielding degree was 10%.

[0088] Instruments and methods for XPS testing: X-ray photoelectron spectroscopy was performed on an ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software from Thermo Scientific. The excitation source was monochromatic Al Kα X-rays with an energy of 1486.6 eV, a power of 150 W, a narrow scan with a penetration energy of 30 eV, and a basic vacuum of 6.5 × 10-10 mbar during the analysis. Data processing was performed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module. The samples were dried in a helium atmosphere at 150 ° C and 1 standard atmosphere for 3 hours before testing.

[0089] Electrochemical testing instrument: CT3002A battery testing system of Wuhan Blue Electric Electronics Co., Ltd.

[0090] Sand mill model: VB0.6Q nano sand mill produced by Suzhou Weige Nano Technology Co., Ltd.

[0091] Spray dryer model: B-290 from BUCHI, Switzerland, including B-295 inert gas circulation device, using nitrogen as carrier gas for spray drying.

[0092] The raw materials in the following examples, unless otherwise specified, were commercially available.

[0093] Preparation Example 1

[0094] (1) 50 g of silicon powder (single crystal silicon, silicon purity of 99.999%, average particle size of 2 to 10 μm) was added to 1500 mL of isopropanol solution containing 25 g of ascorbic acid, and the mixture was sand-milled in a sand mill under nitrogen protection for 8 h, and then taken out to obtain ascorbic acid-coated nano-silicon slurry;

[0095] (2) taking 100 mL of the nano-silicon slurry prepared in step (1), stirring and dispersing the mixture, adding 0.67 g of dopamine hydrochloride, and continuing stirring at room temperature for 1 h to obtain a nano-silicon slurry coated with dopamine and ascorbic acid by in-situ reaction, and then spray drying the mixture to obtain a modified nano-silicon precursor;

[0096] (3) The obtained nano-silicon precursor was placed in a porcelain boat and heated in a tube furnace at 5°C min under an argon atmosphere. -1 The temperature was raised to 900°C at a rate of 1.5°C, then kept at that temperature for 3 hours, and naturally cooled to room temperature to obtain modified nano-silicon;

[0097] (4) Take 1.14 g of the modified nano-silicon prepared in step (3), add 18.86 g of spherical artificial graphite, and mix them thoroughly in a planetary ball mill to obtain the lithium ion battery negative electrode material of the present invention.

[0098] Preparation Example 2

[0099] (1) 50 g of silicon powder (single crystal silicon, silicon purity of 99.999%, particle size of 2 to 10 μm) was added to 1500 mL of isopropanol solution containing 50 g of citric acid, and the mixture was sand-milled in a sand mill under nitrogen protection for 8 h, and then taken out to obtain a citric acid-coated nano-silicon slurry;

[0100] (2) taking 100 mL of the nano-silicon slurry prepared in step (1), stirring and dispersing the mixture, adding 3.33 g of dopamine hydrochloride, and continuing stirring at room temperature for 1 h to obtain a nano-silicon slurry coated with dopamine and citric acid in situ reaction, and then spray drying the mixture to obtain a modified nano-silicon precursor;

[0101] (3) Place the modified nano-silicon precursor into a porcelain boat and heat it in a tube furnace at 5°C min under an argon atmosphere. -1 The temperature was raised to 800°C, then kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain modified nano-silicon;

[0102] (4) Take 1.40 g of the modified nano-silicon prepared in step (3), add 18.60 g of spherical artificial graphite and mix them thoroughly in a planetary ball mill to obtain the lithium ion battery negative electrode material of the present invention.

[0103] Preparation Example 3

[0104] (1) 50 g of silicon powder (single crystal silicon, silicon purity of 99.999%, average particle size of 2 to 10 μm) was added to 1500 mL of isopropanol solution containing 50 g of L-malic acid, and the mixture was sand-milled in a sand mill under nitrogen protection for 8 h, and then taken out to obtain L-malic acid-coated nano-silicon slurry;

[0105] (2) taking 100 mL of the nano-silicon slurry prepared in step (1), stirring and dispersing it thoroughly, adding 1.67 g of dopamine hydrochloride, and continuing to stir for 1 h to obtain a nano-silicon slurry coated with dopamine and L-malic acid by in-situ reaction, and then spray drying to obtain a modified nano-silicon precursor;

[0106] (3) Place the modified nano-silicon precursor into a porcelain boat and heat it in a tube furnace at 5°C min under an argon atmosphere. -1 The temperature was raised to 800°C, then kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain modified nano-silicon;

[0107] (4) Take 1.35 g of the modified nano-silicon prepared in step (3), add 19.33 g of spherical artificial graphite, and mix them thoroughly in a planetary ball mill to obtain the lithium ion battery negative electrode material of the present invention.

[0108] Comparative Preparation Example 1

[0109] A negative electrode material for a lithium ion battery is prepared according to the method of Preparation Example 1, except that step (2) is not included, and the nano-silicon slurry in step (1) is directly spray-dried to obtain a nano-silicon precursor, and then steps (3) and (4) are performed to obtain a negative electrode material for a lithium ion battery.

[0110] Comparative Preparation Example 2

[0111] A negative electrode material for a lithium ion battery was prepared according to the method of Preparation Example 1, except that no organic acid was added in step (1), 1.0 g of dopamine hydrochloride was added in step (2), and then steps (3) and (4) were performed to obtain a negative electrode material for a lithium ion battery.

[0112] Test Examples 1 to 3 are used to illustrate the electrochemical performance of the lithium ion battery negative electrode material of the present invention.

[0113] Test cases 1 to 3

[0114] The negative electrode materials of lithium-ion batteries prepared in Preparation Examples 1 to 3 were mixed with acetylene black and a binder (the binder was sodium carboxymethyl cellulose and styrene-butadiene rubber, the mass ratio of the two was 1:1) at a mass ratio of 8:1:1 to form a slurry, which was then coated on a copper foil and dried to obtain an electrode sheet. The prepared electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, and a Celgard 2400 type separator was selected, 1 mol L -1 LiPF 6The electrolyte was a mixed solvent of ethylene carbonate: dimethyl carbonate: diethyl carbonate = 1:1:1. The button half-cell was assembled in a glove box and the battery was charged and discharged using a blue power system. The parameters were set as follows: current density 100 mA g -1 , the voltage range is 0.01~1.5V.

[0115] The test results are shown in Table 1.

[0116] Comparative test examples 1 to 2

[0117] The test was carried out according to the method of Test Example 1, except that the negative electrode materials of the lithium-ion battery were replaced by the products of Comparative Preparation Examples 1 to 2 respectively.

[0118] Table 1

[0119]

[0120] The mass fraction of modified nano-silicon in the negative electrode materials of lithium-ion batteries prepared in Preparation Examples 1 to 3 is 4% to 7%. As can be seen from Test Examples 1 to 3 in Table 1, the first charge specific capacity is 465.9 mA hg -1 ~480.9mA hg -1 The first coulombic efficiency is 85.4% to 88.2%, and the capacity retention rate after 300 cycles is 88.7% to 89.6%, indicating that the lithium ion battery negative electrode material of the present invention has a high first charge specific capacity, a high first coulombic efficiency, a high cycle capacity retention rate, and excellent comprehensive performance.

[0121] The spherical artificial graphite in the embodiment is a commercial graphite negative electrode material. When it is used as a negative electrode material for a lithium ion battery, according to the test method and conditions in the test example of the present invention, its first coulomb efficiency is 85.7%, and the first charge specific capacity is 355.8 mA hg -1 Compared with the commercial graphite negative electrode material, the lithium ion battery negative electrode material of the present invention has significantly improved the initial charge specific capacity and is not affected by silicon doping. The initial coulomb efficiency is equivalent to or higher than that of the commercial graphite negative electrode material. Moreover, the negative electrode material of the present invention has a low silicon doping content and has little impact on the cost.

[0122] It can be seen from Test Examples 1 to 3 and Comparative Test Examples 1 to 2 in Table 1 that the first coulombic efficiency and cycle capacity retention rate of Test Examples 1 to 3 are significantly higher than those of Comparative Test Examples 1 to 2, indicating that the modified nano-silicon of the present invention has better blending performance.

[0123] Figure 1The transmission electron microscope image of the modified nano silicon prepared according to the method of the present invention shows that the silicon surface is coated with a 3nm to 8nm thick heterogeneous carbon layer, the inner layer has no layered structure, which is amorphous carbon, and the outer layer has a distinct layered structure with an interlayer spacing of about 0.33 nanometers, which is graphene. From the 300 cycle capacity retention rate of the negative electrode material of the lithium ion battery in Table 1, it can be seen that the heterogeneous carbon layer structure unique to the modified nano silicon of the present invention is more beneficial to improving the performance of the negative electrode material of the lithium ion battery, especially making the cycle performance more stable.

[0124] Figure 2 The photoelectron spectrum of the modified nano-silicon prepared according to the method of the present invention shows that the nitrogen species on its surface are mainly pyrrole nitrogen. The test results show that the molar fraction of pyrrole nitrogen is above 70% based on the total molar amount of nitrogen species.

[0125] Figure 3 This is the first charge and discharge curve of the negative electrode material prepared according to the method of Preparation Example 1.

[0126] Figure 4 3 is a transmission electron microscope image of the modified nano-silicon obtained when dopamine is not used compared with the method of the present invention. Under the transmission electron microscope, it can be seen that the carbon coating layer has no layered structure and is amorphous carbon.

[0127] Figure 5 3 is a transmission electron microscope image of modified nano-silicon obtained when the first carbon source is not used compared with the method of the present invention. Under the transmission electron microscope, it can be seen that the carbon coating layer has no layered structure and is amorphous carbon.

[0128] Figure 6 This is the XRD pattern of the negative electrode material prepared according to the method of Preparation Example 1.

[0129] Figure 7 This is the charge and discharge cycle curve of the negative electrode material prepared according to the method of Preparation Example 1.

Claims

1. A negative electrode material for a lithium-ion battery, comprising modified nano-silicon and graphite, wherein the modified nano-silicon is nano-silicon with a heterogeneous carbon layer coated on the outer surface, the inner layer of the heterogeneous carbon layer is amorphous carbon, and the outer layer is graphene.

2. The negative electrode material according to claim 1, characterized in that Based on the negative electrode material, the mass fraction of the modified nano silicon is 1% to 25%, and the mass fraction of the graphite is 75% to 99%; preferably, the mass fraction of the modified nano silicon is 1% to 8%, and the mass fraction of the graphite is 92% to 99%.

3. The negative electrode material according to claim 1, characterized in that In the modified nano silicon, the mass fraction of silicon is 60% to 80%, and the mass fraction of carbon is 10% to 30%.

4. The negative electrode material according to claim 1, characterized in that The heterogeneous carbon layer contains nitrogen. In the XPS N1s analysis of the modified nano-silicon, the molar fraction of pyrrole nitrogen is 70% to 90% based on the total molar amount of nitrogen species.

5. The negative electrode material according to claim 1, characterized in that: The median particle size of the modified nano-silicon is 5nm to 150nm.

6. The negative electrode material according to claim 1, characterized in that: The thickness of the heterogeneous carbon layer is 3nm-8nm.

7. The negative electrode material according to claim 1, characterized in that: The thickness of the graphene is 1nm to 6nm.

8. A method for preparing a negative electrode material for a lithium ion battery, comprising: S1 disperses elemental silicon in a solution containing a first carbon source, and obtains nano-silicon slurry by mechanical crushing; The first carbon source is a hydroxyl-containing organic carboxylic acid or carboxylic acid ester; S2: adding dopamine or its ammonium salt to the nano-silicon slurry obtained in S1 to react and obtain a nano-silicon precursor; S3 calcines the nano-silicon precursor in S2 at high temperature under an inert gas to obtain modified nano-silicon; S4 mixes the modified nano-silicon prepared in S3 with graphite to obtain the negative electrode material for the lithium-ion battery.

9. The preparation method according to claim 8, characterized in that: The single-substance silicon is single-crystal silicon or polycrystalline silicon.

10. The preparation method according to claim 8, characterized in that: In S1, the first carbon source is selected from one or more of tartaric acid, citric acid, lactobionic acid, malic acid and ascorbic acid; and the mass ratio of the first carbon source to silicon is 1:0.2 to 1:

5.

11. The preparation method according to claim 8, characterized in that: The mechanized crushing method is sand grinding, and the particle size of silicon after sand grinding is 5nm to 150nm.

12. The preparation method according to claim 8, characterized in that: The mass ratio of the dopamine or its ammonium salt to the first carbon source is 0.3:1 to 1.2:

1.

13. The preparation method according to claim 8, characterized in that: In S2, the solvent is removed after the reaction to obtain the nano-silicon precursor, and the solvent is removed by spray drying.

14. The preparation method according to claim 8, characterized in that: In S3, the temperature of the high temperature calcination is 800°C to 1000°C.

15. The preparation method according to claim 8, characterized in that: In S4, the mass ratio of modified nano-silicon to graphite is 1:3 to 1:99, preferably 1:11.5 to 1:

99.

16. A negative electrode for a lithium ion battery, characterized in that: Contains the negative electrode material according to any one of claims 1 to 7.

17. A lithium ion battery, characterized in that: Contains the negative electrode material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Nano silicon-carbon composite material as well as preparation method and application thereof

    CN119092652A